1H-NMR-based metabolomics approach to understanding the drying effects on the phytochemicals in Cosmos caudatus - Mediani, Ahmed; Abas, Faridah; Khatib, Alfi; Maulidiani, H; Shaari, Khozirah; Choi, Young Hae; Lajis, Nordin (Elsevier, 2012)
medicinal herb to treat several maladies. Proton nuclear magnetic resonance (1H-NMR) combined with principal component analysis (PCA) and partial least-squares analysis (PLS) was applied to distinguish variations among C. caudatus materials processed with various drying techniques. A discriminatory report on the metabolites responsible for the variation between air (AD), oven (OD) and freeze (FD) dryings of C. caudatus samples was successfully achieved using 1H-NMR-based metabolomics. The correlation between antioxidant activity (AA) represented by radical DPPH scavenging activity and metabolite variation among processed samples dried in three different ways was also determined by partial least-squares analysis (PLS). The PCA and PLS scores showed a noticeable and clear separation into three clusters representing the three drying methods by PC1 and PC2, with an eigenvalue of 77.9%. Various assigned 1H-NMR chemical shifts referring to themetabolites responsible for sample variation were ascribed. The identified compounds were β- and α-glucose, chlorogenic acid, catechin, rutin, quercetin, quercetin 3-O-rhamnoside, quercetin 3-O-β-arabinofuranoside and quercetin 3-O-β-glucoside. This research demonstrates thatmost of the identified compounds were present in all samples from the three processing methods. However, there was marked variance in the concentration of the constituents present.